Traffic Data Based Ideal Airport Suggestions Providing Regional Service in Disasters - Emre Demir (Doğal Afetler ve Çevre Dergisi)
This study differs from previous similar studies in three main directions. Firstly, the location of the most suitable facilities that can provide regional service were determined by applying clustering method. Thus, not only one airport facility in a single location serving across the country was determined, which separates this research from the others. Secondly, in the previous studies, Istanbul Airport was not taken into account because it has not been put into service. Therefore, this study takes that particular airport into consideration. Thirdly, optimum solutions for such new situation were produced with more up-to-date data and using a modern optimization method, the tree seed algorithm. As a result of the analyzes made based on traffic data, traffic-based weight coefficients and location data from which transportation distances were obtained, a total of sixteen ideal airports were recommended that can provide service to their regions, especially during emergencies or after any disaster. In accordance with the suggestions of this research, it is expected that progress will be made in minimizing the loss of time and expense, and especially minimizing the loss of life thanks to the services which can be provided by air transportation in any emergency.